(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A quasi experimental research design was adopted to evaluate the effectiveness of cognitive behaviour play therapy on level of self esteem among learning disability school age children were selected through probability random simple sampling technique. post test majority the experimental group was achieved 50 (83%) of learning disability students were getting adequate level of self esteem that there was a significant difference (P<0.05) between experiment and control score. The mean experiment score was 74.20 and standard deviation of 5.15 significant t test level is 7.21.